2002
DOI: 10.1080/00140130210166483
|View full text |Cite
|
Sign up to set email alerts
|

Age differences in perceived workload across a short vigil

Abstract: The main objective of this research was to investigate age differences in the perceived workload associated with the performance of a demanding, high event rate, vigilance task.Younger workers (n = 26) aged 16 to 35 years (M = 27.8) and older workers (n = 24) aged 45 to 65 years (M = 52.2) completed perceived workload scales (NASA-TLX) following a brief practice session (pretest) on the vigilance task, and then again following a test session (posttest) lasting nine minutes. In relation to the vigilance task, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…No significant results emerged from any cognitive variable on performance. These results are consistent with Bunce and Sisa (2002) and Deaton and Parasuraman (1993) findings.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…No significant results emerged from any cognitive variable on performance. These results are consistent with Bunce and Sisa (2002) and Deaton and Parasuraman (1993) findings.…”
Section: Discussionsupporting
confidence: 83%
“…In this regard, Bunce and Sisa (2002) analysed the effects of age on subjective mental workload measured by the NASA-TLX during the course of a vigil and how do workload perceptions relate to performance on a vigilance task. They showed a certain interest, albeit indirect, in studying the effects of this type of characteristic on subjective estimations of mental workload when they discussed the deterioration of cognitive ability resulting from aging.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the women perceived higher physical demands at work than men (Nyga˚rd et al 1997). Bunce and Sisa (2002) ascertained the differences with age in perceived workload across short vigilance tasks. They indicated that, while older participants were able to maintain the same performance level as their younger colleagues, they perceived a greater increase in the workload associated with that demand for vigilance.…”
Section: Introductionmentioning
confidence: 99%
“…where e is the elements included in NASA-TLX and w represents the weight of individual element (Bunce & Sisa, 2002).…”
Section: Designmentioning
confidence: 99%